2020
DOI: 10.1002/mgg3.1237
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant in the neutrophil cytosolic factor 2 (NCF2) gene results in severe disseminated BCG infectious disease: A clinical report and literature review

Abstract: Background Chronic granulomatous disease (CGD) is a rare primary immunodeficiency disorder (PID) affecting NADPH oxidase activity. The rarest form of the disease is considered to be caused by NCF2 gene bi‐allelic variant. Here, we report the clinical and molecular characterization of a patient presenting with early‐onset severe disease due to bi‐allelic NCF2 variant. Methods Gene mutational analysis was performed by whole‐exome and Sanger sequencing. Results The patient presented with a history of fever and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…13,14 The results are presented as the stimulation index (SI), which is the ratio of the mean fluorescence intensity (MFI) of stimulated granulocytes to unstimulated granulocytes. [10][11][12]15,16 We always evaluated healthy individuals as positive controls and confirmed that the consistent results were obtained.…”
Section: Analysis Of the Production Of Reactive Oxygen Speciessupporting
confidence: 76%
See 3 more Smart Citations
“…13,14 The results are presented as the stimulation index (SI), which is the ratio of the mean fluorescence intensity (MFI) of stimulated granulocytes to unstimulated granulocytes. [10][11][12]15,16 We always evaluated healthy individuals as positive controls and confirmed that the consistent results were obtained.…”
Section: Analysis Of the Production Of Reactive Oxygen Speciessupporting
confidence: 76%
“…After erythrocyte lysis, the production of ROS by granulocytes was quantified by measuring intracellular rhodamine with FACSCalibur flow cytometer (BD Bioscience, Tokyo, Japan), as previously described 13,14 . The results are presented as the stimulation index (SI), which is the ratio of the mean fluorescence intensity (MFI) of stimulated granulocytes to unstimulated granulocytes 10–12,15,16 . We always evaluated healthy individuals as positive controls and confirmed that the consistent results were obtained.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations